Isolasi dan Identifi kasi Senyawa Fenolik dari Daun Macaranga hispida Blume Mull.Arg - Megawati Megawati; Sofa Fajriah; Galuh Widyawati; Akhmad Darmawan (Fakultas Farmasi Universitas Pancasila, 2020)
Continuation of research on Macaranga plant has been conducted. In this study, the totalphenol content (TPC) of Macaranga hispida Blume Mull. Arg leaves extracts were investigated. Gallicacid (1) and methyl gallate (2) have been isolated from the ethyl acetate fraction which highest phenoliccontent (8.41 mg GAE/g). Serial techniques of chromatographic and spectroscopic methods, namelyextraction, fractionation, purifi cation, FTIR, LCMS, and FT-NMR were used to isolate and identify theisolates. Cytotoxicity of compound 1 and 2 against P-388 cell line showed that compound 2 has higheranticancer activity compared to compound 1 with IC50 value of 75.53 μg/mL.